HADHANAH PASCA PERCERAIAN DALAM ISLAM - Paryadi, Paryadi (Moderation | Journal of Islamic Studies Review, 2022)
Happiness for people who are already married is getting children. Children have rights that are the obligation of parents to fulfill them. However, when the family ark experiences a storm of divorce, children's rights, especially hadhanah, are often neglected. Therefore, this article analyzes and discusses the position of children after divorce in Islamic law. Actually, Islam regulates in depth in the Qur'an, hadith and the words of scholars about the hadhanah of children when their parents divorce. For this reason, it is very necessary to provide special education to the community and especially the role of the government in implementing the agreed regulations.